Inhibitory Effect of Myricetin on Melanoma Cells (A375) - Abdolmaleki, Fereshte; Gheibi, Nematollah; Ahmadpour Yazdi, Hossein (Novelty in Biomedicine, 2017)
Background: Cancer, a major cause of mortality worldwide, is a group of diseases distinguished by uncontrolled growth and expansion of abnormal cells. According to American Cancer Society, melanoma, a kind of skin cancer, is one of the most prevalent cancers. The side effects of chemical treatment developed more demands on natural products. Flavonoids, polyphenol compounds, with anticancer and antioxidant activity attracted more attention to themselves. Materials and Methods: Through this investigation the effect of myricetin on cell proliferation was determined by MTT (Methylthiazolyl diphenyl-tetrazolium bromide) assay. A375 cell lines were seeded in a 96 wells plate and were exposed to different concentrations of myricetin (10, 15, 20, 40, 60, 80, and 100µΜ). After considered times, the MTT solution was added, then the viability of cells was detected by measuring the absorbance on 570 and 630 nm. Results: Our finding showed that low concentration of myricetin (up to 25µM) has no toxicity effect. Also the result confirmed the IC50 of myricetin on melanoma cells for three ordered period (24, 48, 72 hours) as following: 50, 40, 35µΜ, respectively. Conclusion: According to this research, myricetin has anti-proliferative effect on melanoma cells, which can be used as a therapeutic agent. We hope that this study could be used as a mile stone in future researches to acquire confirmative results.